High-throughput DNA sequencing of microbiota at interproximal sites - Carda-Diéguez, Miguel; Bravo-González, Luis Alberto; Morata, Isabel María; Vicente, Ascensión; Mira, Alex (Journal of oral microbiology, 2020)
Objective: The oral microbiota has been deeply studied by high-throughput sequencing techniques. However, although the interproximal regions have one of the highest caries rates in the oral cavity, information about the bacterial composition at those sites is scarce. Methods: In this study, we used 16S rRNA Illumina sequencing to describe the microbiota associated to interproximal regions at two time points. In addition, dental plaque samples at the vestibular and lingual surfaces from the same teeth were also analysed at the two time points. Results: Interproximal-associated microbiota was found to be similar to already described bacterial communities in other mouth niches. Streptoccocus, Veillonella, Rothia, Actinomyces, Neisseria, Haemophilus and Fusobacterium were the most abundant genera in this oral region. Statistical analyses showed that the microbiota from interproximal sites was more similar to that sampled from the vestibular surfaces than to the lingual surfaces. Interestingly, many potentially cariogenic bacteria such as Scardovia, Atopobium or Selenomonas were over-represented in the interproximal regions in comparison with vestibular and lingual sites. Conclusion: The microbiota at interproximal regions appears to be specific and stable through time. Potentially pathogenic bacteria may increase caries development risk and gingival inflammation at those sites.